2022
DOI: 10.1002/er.7964
|View full text |Cite
|
Sign up to set email alerts
|

CO x ‐free catalytic decomposition of methane over solution combustion synthesis derived catalyst: Synthesis of hydrogen and carbon nanofibers

Abstract: Summary The catalyst for decomposition of methane to carbon nanofibers and hydrogen was prepared using the solution combustion technique. Dynamics of change of temperature of solution (gel) during the passing of redox reaction of synthesis of catalyst was found experimentally. Testing of catalyst was carried out in a flow through installation. Catalyst with high content of active component 90Ni‐10Al2O3 (wt%) was tested in a reaction of methane decomposition in a temperature range 535°С to 675°С and pressures 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…When the ratio of (catalyst weight)/pressure was kept constant (▲), the crystallite size was slightly larger than that when the catalyst weight was kept constant at 15 g (●): the higher the pressure, the larger the crystallite size of α-Fe was. In the case of Ni, also, it has been reported that the metallic crystallite size tends to increase under pressure, although the correlation is weak …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…When the ratio of (catalyst weight)/pressure was kept constant (▲), the crystallite size was slightly larger than that when the catalyst weight was kept constant at 15 g (●): the higher the pressure, the larger the crystallite size of α-Fe was. In the case of Ni, also, it has been reported that the metallic crystallite size tends to increase under pressure, although the correlation is weak …”
Section: Resultsmentioning
confidence: 99%
“…In the case of Ni, also, it has been reported that the metallic crystallite size tends to increase under pressure, although the correlation is weak. 6 The sizes of α-Fe crystallite after 42 h of reaction with catalyst weight = 15 g, CH 4 flow rate = 300 mL/min, and pressure = 1 atm and after 14 h of reaction with 45 g of catalyst weight, 900 mL/min CH 4 flow rate, and 3 atm pressure are also shown in Figure 8. The size of α-Fe crystallite was found to decrease with time, which is also consistent with Wang's report.…”
Section: Xrd Measurement Of Deposited Carbonmentioning
confidence: 96%
See 3 more Smart Citations